Integrated ONT Full-Length Transcriptome and Metabolism Reveal the Mechanism Affecting Ovulation in Muscovy Duck (Cairina moschata) - Lin, Junyuan; Ge, Liyan; Mei, Xiang; Niu, Yurui; Chen, Chu; Hou, Shuisheng; Liu, Xiaolin (Frontiers in Veterinary Science, 2022)
Ovulation is a complicated physiological process that is regulated by a multitude of different pathways. In comparison to mammalian studies, there are few reports of ovulation in Muscovy ducks, and the molecular mechanism of ovarian development remained unclear. In order to identify candidate genes and metabolites related to Muscovy duck follicular ovulation, the study combined Oxford Nanopore Technologies (ONT) full-length transcriptome and metabolomics to analyze the differences in gene expression and metabolite accumulation in the ovaries between preovulation (PO) and consecutive ovulation (CO) Muscovy ducks. 83 differentially accumulated metabolites (DAMs) were identified using metabolomics analysis, 33 of which are related to lipids. Combined with data from previous transcriptomic analyses found that DEGs and DAMs were particularly enriched in processes including the regulation of glycerophospholipid metabolism pathway, arachidonic acid metabolic pathway and the steroid biosynthetic pathway. In summary, the novel potential mechanisms that affect ovulation in Muscovy ducks may be related to lipid metabolism, and the findings provide new insights into the mechanisms of ovulation in waterfowl and will contribute to a better understanding of changes in the waterfowl ovarian development regulatory network.